Fatigue life of automotive rubber jounce bumper - Sidhu, R. S.; Ali, Aidy (2010)
It is evident that most rubber components in the automotive industry are subjected to repetitive loading. Vigorous research is needed towards improving the safety and reliability of the components. The study was done on an automotive rubber jounce bumper with a rubber hardness of 60 IRHD. The test was conducted in displacement-controlled environment under compressive load. The existing models by Kim, Harbour, Woo and Li were adopted to predict the fatigue life. The experimental results show strong similarities with the predicted models.